How do you simplify #2^2 + 2^3 [4(3-1)(4+6)-13]#?

1 Answer
May 15, 2016

Answer:

#2^2+2^3[4(3-1)(4+6)-13]=540#

Explanation:

The order of operations in such cases is given by the abbreviation PEMDAS, which stands for "Parentheses, Exponents, Multiplication and Division, and Addition and Subtraction", in that order.

In #2^2+2^3{4(3-1)(4+6)-13}#, we should first solve parentheses and then other operations in the above order. This gives us

#2^2+2^3[4(3-1)(4+6)-13]#

= #2^2+2^3*[4*2*10-13]#

= #2^2+2^3*[80-13]#

= #4+8*67#

= #4+536#

= #540#